A Multi-Agent Ad Hoc On-Demand Distance Vector for Improving the Quality of Service in MANETs - Mostafa S.A.; Tang A.Y.C.; Hassan M.H.; Jubair M.A.; Khaleefah S.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Energy utilization; Mobile telecommunication systems; Multi agent systems; Power management (telecommunication); Quality of service; Robotics; Routing protocols; Wireless telecommunication systems; Ad hoc on demand distance vector; Computing devices; Destination nodes; Minimum delay; Mobile ad-hoc network (MANETs); Mobile communications; Number of hops; Wireless technologies; Mobile ad hoc networks